Mapping brain activity associated with emotion. - Robinson, Robert G. (American Journal of Psychiatry, 1995)
A commentary on Mark S. George et al.'s “Brain Activity During Transient Sadness and Happiness in Healthy Women,” which appeared in this issue. George et al. report on changes in regional cerebral blood flow measured by H215O and positron emission tomography in 11 healthy adult women who induced happiness, sadness, or neutral emotion by recalling affect-laden or neutral memories while viewing congruent happy, sad, or neutral human faces. It is principally emotional change that lies at the heart of human suffering associated with mental disorders and constitutes the focus of much of psychiatrists' work in psychotherapy and pharmacotherapy. The work of George at al. represents an important step in validating the role of the limbic system in emotion and identifying the regional structures that mediate different types of emotion. Important questions raised by studies of emotional activation in normal subjects in terms of methodology and the generalizability of findings are discussed.